Correlation of Food Consumption Behaviors and Nutritional Status with Risk of Dementia in Older People - Chamnongchit, Sirirat; Piaseu, Noppawan (Journal of The Royal Thai Army Nurses, 2020)
This descriptive correlational research used secondary data from the community survey project for establishment of the learning and development center for older people health and palliative care of end-stage patients of the Faculty ofMedicine, Ramathibodi Hospital, Mahidol University aimed to 1) describe the risk of dementia and 2) investigate the relationship of food consumption behaviors and nutritional status with risk of dementia in older people. The sample included 396 older people, residing in communities, Prachuap Khiri Khan province. Data were analyzed using descriptive statistics, Spearman rank correlation and Point biserial correlation. Results revealed that 8.8 % of the older people were at risk of dementia. Food consumption behaviors associated withrisk of dementia included adding chili powder in almost foods (rpb = -.172, p =.001) and avoiding foods containing high sugar, fat, and sodium (rpb = -.101,p = .044). Nutritional status associated with risk of dementia included mini nutritional assessment scores (rs = .153, p = .002), body mass index (rs = .112, p = .026) and handgrip strength (rs= .267, p <.001). Results suggest that should provide care for older people to reduce foods containing high sugar, fat, and sodium, control body weight, and enhance muscle strength in order to achieve appropriate nutrition status and decrease risks of dementia among them.